2021
DOI: 10.1186/s12882-021-02418-7
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related acute kidney injury at high altitude: a retrospective observational study in a single center

Abstract: Background Pregnancy-related acute kidney injury (Pr-AKI) is associated with maternal and fetal morbidity and mortality. There are few studies focusing on Pr-AKI at high altitude in the literature. Objectives to investigate the incidence, etiology, clinical features and maternal-fetal outcomes of Pr-AKI in women living at high altitude. Methods 6,512 pregnant women attending the Department of Obstetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…This finding is similar to another local study. 10 However the reported proportion of eclampsia in the current study is very low compared to many other studies where the stated percentages are 35%, 17 44.5%, 13 56%, 12 and 73%. 18 These high rates are basically due to reduction in number of cases of postpartum hemorrhage attributed to advanced health systems in contrast to high prevalence of obstetrical hemorrhage in the region of current study.…”
Section: Discussioncontrasting
confidence: 60%
“…This finding is similar to another local study. 10 However the reported proportion of eclampsia in the current study is very low compared to many other studies where the stated percentages are 35%, 17 44.5%, 13 56%, 12 and 73%. 18 These high rates are basically due to reduction in number of cases of postpartum hemorrhage attributed to advanced health systems in contrast to high prevalence of obstetrical hemorrhage in the region of current study.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the specific causes of AKI were not identified, the authors suggested that acute systemic hypoxia and long-term renal hypoperfusion may have been the causes of renal injury ( Yijiang et al, 2013 ). In another study, high altitude was suggested to have an adverse influence on hypertensive disorders of pregnancy-related AKI, with earlier termination of pregnancy and a higher likelihood of stillbirth/neonatal death ( Li et al, 2021 ).…”
Section: Pathological Changesmentioning
confidence: 99%
“…Caution, careful consideration, and more research are needed for pregnant people traveling to high altitude. There are well-documented risks to low-altitude dwellers residing at high altitude for their entire pregnancy, including preeclampsia, eclampsia, hypertension of pregnancy, placenta previa, placental abruption, and preterm labor (4)(5)(6)(7)(8)(9)(10)(11). Fetal complications also are increased in this population, including small for gestational age, intrauterine growth retardation (IUGR), neonatal respiratory distress, pulmonary hypertension, and stillbirths but not congenital malformations (4,5,7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…There are well-documented risks to low-altitude dwellers residing at high altitude for their entire pregnancy, including preeclampsia, eclampsia, hypertension of pregnancy, placenta previa, placental abruption, and preterm labor (4)(5)(6)(7)(8)(9)(10)(11). Fetal complications also are increased in this population, including small for gestational age, intrauterine growth retardation (IUGR), neonatal respiratory distress, pulmonary hypertension, and stillbirths but not congenital malformations (4,5,7,(9)(10)(11). Furthermore, in high-altitude dwellers, infant birth weight decreases with altitude, and lower birth weight is associated with greater health complications in infancy and beyond (9,12).…”
Section: Introductionmentioning
confidence: 99%